Misconduct Among Postgraduate Students in African Universities - Andoh, Harris (International Higher Education, 2025)
Since the early 2000s, African universities have expanded postgraduate education as part of their mission to drive knowledge production, human capital, and national development. Growth through part-time, weekend, and MBA programs has widened access but also fostered widespread misconduct. Plagiarism, contract cheating, falsified research, and collusion are increasingly reported, often in the context of weak supervision and lax enforcement. Drawing on evidence from Ghana, Kenya, South Africa, Zambia, and Nigeria, this article shows how misconduct erodes graduate quality and the credibility of African degrees. It calls for ethical reforms, stronger accountability, and robust quality assurance to safeguard the integrity of postgraduate education.